Implikasi Pembelajaran Khot Imla’ terhadap Keterampilan Menulis Al-Qur’an Siswa Madrasah Aliyah Kudus - Cahyaningsih, Putri Sabita; Noor Fuad, Ai Fatimah (Attractive : Innovative Education Journal, 2024)
This research aims to find out the extent of students' writing skills at MA Ma'ahid Kudus before and after using the Khot Imla' method, and to find out whether the Khot Imla' method is effective for improving Al-Qur'an writing skills. This study uses a qualitative method. Primary data was taken from interviews with study teachers and their students. and secondary data was taken from Madrasah Aliyah MA'AHID KUDUS documentation data. After interviewing the subject teachers, then interview the students and see the results of the existing document data and the results of the written tests that have been carried out. The results of this research, by studying and practicing khot learning, students can write letters and sentences well and correctly through short sentences written repeatedly, by using the Naskhi khot type students can easily imitate the form and writing of Qur'anic sentences well and Correct. By getting used to writing sermons, students are used to writing Arabic sentences, so once they are given imla' (dictation) lessons, students can write Arabic sentences that they hear properly and correctly. Keywords: Implikasi Pembelajaran, Khot Imla’, Keterampilan, Menulis Al-Qur’an